Periostin: A Matricellular Protein With Multiple Functions in Cancer Development and Progression - González-González, Laura; Alonso, Javier (Frontiers in Oncology, 2018)
Tumor microenvironment is considered nowadays as one of the main players in cancer development and progression. Tumor microenvironment is highly complex and consist of non-tumor cells (i.e. cancer-associated fibroblast, endothelial cells or infiltrating leucocytes) and a large list of extracellular matrix proteins and soluble factors. The way in that microenvironment components interact among them and with the tumor cells themselves is very complex and only partially understood. However, it is now clear that these interactions govern and modulate many of the cancer hallmarks such as cell proliferation, the resistance to death, the differentiation state of tumor cells, their ability to migrate and metastasize and the immune response against tumor cells. One of the microenvironment components that has emerged in the last years with strength is a heterogeneous group of multifaceted proteins grouped under the name of matricellular proteins. Matricellular proteins are a family of non-structural matrix proteins that regulate a variety of biological processes in normal and pathological situations. Many components of this family such as periostin (POSTN), osteopontin (SPP1) or the CNN family of proteins have been shown to regulate key aspect of tumor biology, including proliferation, invasion, matrix remodeling and dissemination to pre-metastatic niches in other organs. Matricellular proteins can be produced by tumor cells itself or by other tumor-associated cells, and their synthesis can be affected by intrinsic and/or extrinsic tumor cell factors. In this review, we will focus on the role of periostin in the development and progression of cancer. We will describe their functions in normal tissues and the mechanisms involved in their regulation. We will analyze the tumors in which their expression is altered and their usefulness as a biomarker of tumor progression. Finally, we will speculate about future directions for research and therapeutic approaches targeting periostin.